A Review of Homomorphic Encryption Algorithm for Achieving Security in Cloud: Review Article - Satyarthi, Abhishek; Sharma, Sanjiv (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing has created a brief exchange in code paradigm and being extraordinarily new generation however has been followed extensive through numerous groups and character for his or her computing wants. Definition of Cloud Computing is definitely unique from definitions provided thru researchers. Cloud computing is emerging paradigm gives various IT associated offerings. The safety and privacy are maximum critical elements that inhibits the boom of cloud computing. Security factors are reasons behind lesser amount of actual instances and business enterprise associated cloud applications in assessment to consumer related cloud software program. “Cloud computing can be a model for permitting omnipresent, on hand, on-name for Network get admission to to a shared pool of configurable computing sources (e.g., networks, servers, storage, applications, and services) that may be rapid provisioned and discharged with tokenism manage strive or service organization interaction. This cloud model includes five critical traits, three service fashions (Software as a Service (SaaS). Platform as a Service (PaaS). Infrastructure as a Service (IaaS) and 4 education fashions (Private, Community, Public and Hybrid varieties of cloud)”. The developing pace of cloud is as a substitute brief.